Perspectives Readings on Contemporary American Government [and] Teacher's Guide. - Close Up Foundation, Alexandria, VA.; Close Up Foundation, Alexandria, VA. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1997)
This student reader accompanies a teacher's guide of the same name. The essays in this book provide firsthand perspectives on how the federal government works. Essays by President Bill Clinton, Speaker of the House Newt Gingrich, justices of the Supreme Court, journalists, lobbyists, and others who take an active role in this nation's democracy are included. Case studies accompany each section and examine particular topics in depth. The sections of the book include: (1) "The Constitution"; (2) "The Congress"; (3) "The Presidency"; (4) "The Bureaucracy"; (5) "The Judiciary"; (6) "The Media"; (7) "Interest Groups"; and (8) "The People." The teacher's guide contains the following for each unit: objectives; key terms; suggestions for motivating students; student activities; and enrichment activities. Student handouts are included. (EH)
Availability: Close Up Foundation, 44 Canal Center Plaza, Alexandria, VA 22314-1592; Tel: 800-256-7387 (Toll Free); Web site: http://www.closeup.org ($13.95 student text; $15.95 teacher guide).
Practitioners.
Students.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizenship; Citizenship Education; Civics; Democracy; Instructional Materials; Political Science; Secondary Education; Social Studies; United States Government (Course); United States History; Guides, Classroom -- Learner; Guides, Classroom -- Teacher